486PPhase II study of low-dose afatinib maintenance treatment for patients with EGFR-mutated non-small cell lung cancer (NJLCG1601). (24th November 2019) - Morita, M; Nakamura, A; Tanaka, H; Saito, R; Inoue, S; Harada, T; Yamada, T; Nakagawa, T; Jingu, D; Sugawara, S
Abstract: Background: Afatinib is a 2 nd generation EGFR-TKI and has been a standard first line treatment for patients (pts) with advanced NSCLC with EGFR mutations. Afatinib has good efficiency, whereas afatinib has severe adverse events (AEs) and often lead to discontinuation of treatment or a dose reduction. NJLCG1601 was conducted to evaluate the efficacy of low-dose afatinib maintenance treatment. Methods: EGFR-TKI-naïve stage III / IV / recurrent NSCLC pts harboring EGFR mutations (exon 19 deletion or exon 21 L858R or minor mutation) were enrolled. Pts received afatinib 40mg orally once a day. When prescribed AEs (grade ≧ 2 in CACAE ver 4.0) or unacceptable AEs occurred, a dose of afatinib was reduced from 40mg to 30mg, 30mg to 20mg. The treatment was continued until disease progression, occurrence of intolerable severe AEs, or withdrawal of consent. The primary endpoint was 1-year progression free survival (PFS) rate. Secondary endpoints were PFS, overall response rate (ORR), the incidence of AEs, and the incidence of grade ≧ 3 AEs. Assuming a threshold 1-year PFS rate of 42% and an expected 1-year PFS rate of 63%, a total of 26 pts was required to have 90% power at a two-tailed alpha of 0.05. This is a subset analysis of patients with adenocarcinoma in NJLCG1601 study (Trial Identifier, UMIN000020688). Results: Between Apr 2016 and Sep 2017, 30 pts were enrolled. Among 30 patients, 28 patients (93%) were adenocarcinoma. Pts characteristics were as follows: median ages, 70 years (range 46-79 years); proportion of males, 43%; clinical stage, IV 61% and post-op 39%; EGFR mutation types, exon 19 deletion 54%, ex21 L858R 36%, and minor mutations 11%. 1-year PFS rate was 53.6% (95% CI, 33.8-69.8), median PFS was 13.0 months, and ORR was 78.6%. Dose reductions occurred in 86% (24/28). Incidence of all cause grade ≧ 3 was 60% which is smaller than the frequency of Japanese subset in LUX-Lung 3. ILD was occurred in 3 patients and 1 patients died. Treatment-related deaths were observed in 2 pts. Conclusions: Low-dose afatinib maintenance treatment reduced treatment-related adverse events without detracting from the therapeutic efficacy. Legal entity responsible for the study: UMIN000020688. Funding: Has not received any funding. Disclosure: A. Nakamura: Honoraria (self): MSD; Honoraria (self): Chugai; Honoraria (self): AstraZeneca. S. Inoue: Honoraria (self): AstraZeneca; Honoraria (self): Eli Lilly; Honoraria (self): MSD; Honoraria (self): Otsuka Pharmaceutical; Honoraria (self), research funding: Kyorin Pharmaceutical; Honoraria (self): Ono Pharmaceutical; Honoraria (self): GlaxoSmithKline; Honoraria (self): Daiichi Sankyo Company; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): Chugai Pharmaceutical; Honoraria (self): Teijin Pharma; Honoraria (self), research funding: Novartis Pharma; Honoraria (self): Pfizer Inc; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Meiji Seika Pharma. S. Sugawara: Honoraria (self): AstraZeneca; Honoraria (self): Chugai Pharma; Honoraria (self): Nippon Boehringer Ingelheim; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): Pfizer; Honoraria (self): Eli Lilly; Honoraria (self): Novartis; Honoraria (self): Kyowa Hakko Kirin; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Ono Pharmaceutical; Honoraria (self): MSD. All other authors have declared no conflicts of interest.